Associations between caregiver-detected delirium and symptoms of depression and anxiety in family caregivers of critically ill patients: a cross-sectional study - Brianna K. Rosgen; Karla D. Krewulak; Judy E. Davidson; E. Wesley Ely; Henry T. Stelfox; Kirsten M. Fiest (BMC Psychiatry, 2021)
Abstract Background Witnessing delirium can be distressing for family caregivers (i.e., relatives or friends) of critically ill patients. This study aimed to evaluate associations between caregiver-detected delirium in critically ill patients and depression and anxiety symptoms in their family caregivers. Methods Consecutive adult patient-caregiver dyads were enrolled from a 28-bed medical-surgical intensive care unit. Patient delirium was screened for daily by family caregivers using the Sour Seven instrument. Family caregivers completed the Patient Health Questionnaire-9 (PHQ-9) and General Anxiety Disorder-7 (GAD-7) instruments daily to assess their own depression and anxiety symptoms. Response feature analysis was used to handle repeated measures. Descriptive statistics and regression analyses were completed. Results One hundred forty-seven patient-caregiver dyads were enrolled. Clinically significant symptoms of depression and anxiety occurred in 27% and 35% of family caregivers, respectively. Caregiver-detected delirium occurred in 65% of patients, and was not associated with clinically significant caregiver depression (Odds Ratio [OR] 1.4, 95% Confidence Interval [95%CI] 0.6–3.1) or anxiety (OR 1.2, 95%CI 0.6–2.6) symptoms. When stratified by Sour Seven scores, scores 1–3 and 4–9 were associated with increased symptoms of anxiety (OR 3.1, 95%CI 1.3–7.0) and depression (OR 2.6, 95%CI 1.1–6.1) in family caregivers. Caregiver-detected delirium score was associated with severity of family caregiver anxiety symptoms (coefficient 0.2, 95%CI 0.1–0.4), but not depression symptoms (coefficient 0.2, 95%CI -0.0–0.3). Conclusions Caregiver-detected patient delirium was associated with increased depression and anxiety symptoms in family caregivers of critically ill patients. Further randomized research is required to confirm these associations.